THE EFFECT OF USING ENGLISH SPELLING BEE GAME TO ENRICH THE VOCABULARY OF THE SECOND YEAR STUDENTS OF SMPN 40 PEKANBARU - Ade Permata Sari; Afrianto Afrianto; Fadly Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is aimed at finding out the effect of using English Spelling Bee game to enrich the vocabulary of the second year students of SMPN 40 Pekanbaru in academic year 2018/2019. The data were collected from July up to August 2018. The population of this research is the second year students of SMPN 40 Pekanbaru. The number of sample is 30 students selected by using cluster random sampling technique. This research is a pre experimental research with one group pre-test post-test design. The instruments to collect the data were multiple choice test with 20 questions and matching word test with 10 questions. The result of the data analysis showed that the mean score of pre-test is 31.413 while in post-test is 48.063. It shows that the mean score of post-test was higher than pre-test. Hence, there is a significant effect of using English Spelling Bee game to enrich students’ vocabulary. In other words, the alternative hypothesis of this research, “There is any significant effect of using English Spelling Bee game to enrich the vocabulary of the second year students of SMPN 40 Pekanbaru'' is accepted and the null hypothesis is rejected. It can be inferred that teaching vocabulary by using English Spelling Bee game as one of the alternative strategies has an effect on the students’ vocabulary learning.Keywords: English Spelling Bee game, Vocabulary